Features of the Anterior Segment of the Eyeball in Children with 5 Cicatricial Retinopathy of Prematurity According to Ultrasound Biomicroscopy and Optical Coherent Tomography - A. V. Tereshchenko; I. G. Trifanenkova; E. V. Yerokhina (Oftalʹmologiâ, 2020)
Purpose: to study the features of the anatomical and topographic relationships of the eye’s anterior segment structures in children with stage 5 ROP in the cicatricial period with the method of ultrasound biomicroscopy and optical coherent tomography of the anterior segment and to evaluate the possibility of using the data to optimize the surgical treatment of ROP.Patients and methods. For the period 2015–2018 in the Kaluga branch of the Fyodorov Eye Microsurgery, 68 children (118 eyes) with 5 cicatricial ROP stages were examined and treated. Gestational age at birth varied from 24 to 31 weeks, body weight at birth — from 630 to 1600 grams. Age at the time of the survey ranged from 5 to 15 months. All children underwent the complex diagnostic examination, which included biometrics, tonometry, ultrasound ophthalmoscanning in B-mode, as well as UBM and OCT of the anterior segment of the eyeball. The extent of fixation of retrolental opacities to the posterior lens capsule, the presence of cystic cavities and retinal folds at the periphery, traction detachment of the ciliary body were determined. OCT of the eye anterior segment was performed in the presence of iridocorneal contact in order to clarify its length. As a result, a comprehensive detailed assessment made it possible to clarify or reject the characteristics identified by UBM, as well as determine the phasing and develop an individual plan of the operation in each case.Conclusion. The use of complex diagnostic examinations, including UBM and OCT of the eye anterior segment in patients with 5 cicatricial PH stages, allows to optimize the tactics of surgical treatment in the advanced stages of the disease.